DHOK Exerts Anti-Cancer Effect Through Autophagy Inhibition in Colorectal Cancer - Shu, Yuhan; Sun, Xin; Ye, Guiqin; Xu, Mengting; Wu, Zhipan; Wu, Caixia; Li, Shouxin; Tian, Jingkui; Han, Haote; Zhang, Jianbin (Frontiers in Cell and Developmental Biology, 2021)
DHOK (14,15β-dihydroxyklaineanone) is a novel diterpene isolated from roots of Eurycoma longifolia Jack, a traditional herb widely applied in Southeast Asia. It is reported that DHOK has cytotoxic effect on cancer cells, but its anti-cancer mechanism has still been not clear. In our study, we first observed that DHOK inhibits cell proliferation of colorectal cancer cells in a time- and dose-dependent manner. Next, we performed transcriptome sequencing to identify the targets of DHOK and found that autophagy-related signaling pathways are involved under DHOK treatment. Indeed, in DHOK-treated cells, the level of autophagosome marker LC3 and the formation of GFP-LC3 puncta were decreased, indicating the reduction of autophagy. Moreover, confocal microscopy results revealed the lysosomal activity and the fusion of autophagosomes and lysosomes are also inhibited. Our western blotting results demonstrated the activation of mTOR (mammalian target of rapamycin) signaling pathway by DHOK, which may be attributed to the enhancement of ERK and AKT activity. Functionally, activation of autophagy attenuated DHOK-caused cell death, suggesting that autophagy serves as cell survival. In xenograft mouse model, our results also showed that DHOK activates the mOTR signaling pathway, decreases autophagy level and inhibits the tumorigenesis of colon cancer. Taken together, we revealed the molecular mechanism of DHOK against cancer, which demonstrates great potential of DHOK in the treatment of colorectal cancer.